Diffusion of energetic compounds through biological membrane: Application of classical MD and COSMOmic approximations. Issue 1 (2nd January 2019) - Golius, Anastasiia; Gorb, Leonid; Isayev, Olexander; Leszczynski, Jerzy
Abstract : Computational studies of the potential biological impact of several energetic compounds were performed. The most commonly used explosives were considered in the present studies: trinitrotoluene (TNT), 2, 4-dinitrotoluene (2, 4-DNT), 2, 4-dinitroanisole (DNAN), and 5-Nitro-2, 4-dihydro-3H-1, 2, 4-triazol-3-one (NTO). The effect of such factors as ionic strength and presence of DMSO in the water solution on the structure of the membrane were considered using the POPC lipid bilayer as an example. Molecular dynamics (MD) simulations revealed that, even on a short-time scale, the influence of those additives is noticeable, and therefore those factors should always be taken into account. The MD and the COSMOmic approaches were used to elucidate the ability of the energetic compounds to penetrate the living cell. Calculated free energy profiles and partitioning coefficients revealed distributions of the compounds in the lipid bilayer as well as an overall ability to enter the cell. MD in this case provides a better representation of the free energy profile, while the COSMOmic approach works better to predict log( K lipw ) values. The effect of the functional group was observed for the profiles that were obtained using the MD method.